Assessing the Impact of Mandibular Molar Root Length on Success in Supplemental Intraligamentary Injection for Irreversible Pulpitis - Kamali, Marzieh; Parirokh, Masoud; Manochehrifar, Hamed; Nakhaei, Nouzar (Iranian Endodontic Journal, 2024)
Introduction: This study investigates the influence of root length in mandibular molars with irreversible pulpitis on the success of supplemental intraligamentary injection following an inferior alveolar nerve (IAN) block. Various factors, including anatomical location, tooth type, and anesthetic solution, may affect supplemental anesthesia success. Materials and Methods: A total of 251 patients diagnosed with irreversible pulpitis in mandibular first or second molars underwent buccal infiltration anesthesia (4% articaine with 1:100,000 epinephrine) after IAN block injection (3% prilocaine and 0.03 IU/mL of felypressin). Fifty patients experiencing pain during access cavity preparation received supplemental intraligamentary injection (0.3 mL of 2% lidocaine with 1:80,000 epinephrine) at each mesial and distal line angle. The root length of treated teeth was recorded using an apex locator. Data analysis involved independent t-tests, Chi-square tests, and logistic regression. Results: Successful supplemental intraligamentary injection was observed in 21 (42%) out of 50 patients. No significant correlation was found between the mean length of mesiobuccal (P=0.61), mesiolingual (P=0.34), or distal (P=0.60) canals of mandibular molars and the injection’s success. Logistic regression analysis, however, revealed a significant impact of mesiolingual canal length on the success rate [OR 0.09 (0.01-0.79), P=0.030]. Conclusion: The root length of mandibular first and second molars does not significantly affect the success of supplemental intraligamentary injection.